Design, analysis and experiment of a passively adaptive underactuated robotic hand with linkage-slider and rack-pinion mechanisms. (January 2021) - Wang, Daoming; Xiong, Yan; Zi, Bin; Qian, Sen; Wang, Zhengyu; Zhu, Weidong
Highlights: A low-cost, multimode, and passively adaptive five-fingered UADH is developed. Linkage-slider and rack-pinion mechanisms are used for powerful and adaptive grasping. Kinematics and statics of both fingertip grasping and adaptive grasping are presented. The dexterity and grasping performance of the UADH are experimentally evaluated. Abstract: This paper presents the design, analysis and experiment of a passively adaptive five-fingered underactuated dexterous hand (UADH).The UADH has the ability to powerfully grasp objects with different shapes and sizes by using linkage-slider and rack-pinion mechanisms. First, a description of the mechanical design of the UADH, including the transmission scheme, finger and thumb mechanisms, and the overall configuration, is presented in detail. Subsequently, the kinematics and statics of the designed UADH during fingertip grasping and adaptive grasping are described. This paper details the modeling of the contact force of each phalanx, followed by several numerical calculations to reveal the effect of the contact position and bending angle on the contact force. Finally, an experimental platform is established, and several experiments are carried out on the UADH prototype. The results demonstrate that the developed UADH has good dexterity, adaptability and strong fingertip grasping ability, and the results also validate the static contact force model.